The recent decline of Montastraea annularis (complex) coral populations in western Curaçao: a cause for concern? - A. W Bruckner; R. J Bruckner (Revista de Biología Tropical, 2006)
Shallow leeward reefs off the western end of Curaçao are dominated by extensive populations of M. annularis (complex). These species are larger in size (mean= 66 cm diameter) than all other species, with few small colonies (<30 cm) and notable absence of recruits. In 1998, colonies of M. annularis (complex) accounted for more then 45% of all species >10 cm observed within transects, and most exhibited low levels of partial mortality (mean= 22.5%). These species were less abundant (38% of all colonies) in 2005. Partial mortality among live colonies of M. annularis and M. faveolata increased by 85% (mean = 42% partial mortality) and numerous dead colonies of M. faveolata and M. annularis were observed; M. franksi colonies were generally in excellent condition (14% partial tissue mortality). A high prevalence of coral diseases (3-30%) was documented among M. annularis and M. faveolata, while all other species were less frequently affected. Yellow band disease (YBD) emerged shortly after the 1995 bleaching event, and rapidly spread throughout all depths, with the highest prevalence between 1997-1999. YBD caused slow rates of mortality (=1 cm/month), but multiple focal lesions appeared on individual colonies, and these progressively radiated outward as they killed the colonies. By 2005, 44% of the tagged corals were dead; the remainder exhibited active YBD infections (21%) or were in remission (31.6%) but were missing on average >90% of their tissue. Although the incidence of YBD has declined since 2000, white plague (WP) prevalence was unusually high (4-12%) in 2001 and 2005, with affected colonies exhibiting recent mortality of up to 70%. Dead Montastraea spp. surfaces are being colonized by other corals, including poritids, agaricids, and other faviids, while recruits of M. annularis (complex) are absent. If diseases and other biotic stressors persist on these reefs, M. annularis and M. faveolata populations may undergo a decline similar to that observed in the 1980s among Caribbean acroporids. Rev. Biol. Trop. 54 (Suppl. 3): 45- 58. Epub 2007 Jan. 15. Los arrecifes someros a sotavento del oeste de Curaçao están dominados por extensas poblaciones de Montastraea annularis (complejo). Estas especies son mayores en tamaño (promedio= 66 cm de diámetro) que las otras especies, con algunas colonias pequeñas (<30 cm) y una notable ausencia de reclutas. En 1998, las colonias de Montastraea annularis (complejo), representaban más del 45% de todas las especies de >10 cm observadas en transectos y la mayoría exhibió bajos niveles de mortalidad parcial (prom= 22.5%). En el 2005, fueron menos abundantes (38% de las colonias). La mortalidad parcial en colonias vivas de M. annularis y M. faveolata se incrementó en un 85% (promedio= 42% de mortalidad parcial) y se observaron numerosas colonias de M. annularis y M. faveolata muertas; las colonias de M. franski generalmente se encontraron en excelentes condiciones (14% de mortalidad parcial). Se documentó una alta prevalencia de enfermedades de coral (3-30%) en M. annularis y M. faveolata, mientras que las otras especies se vieron afectadas con menor frecuencia. La enfermedad de banda amarilla (BA) emergió poco después del blanqueamiento de 1995 y se dispersó rápidamente en todas las profundidades, alcanzando su mayor prevalencia entre 1997-1999. La BA causó mortalidades lentas (= 1cm/mes), con aparición de múltiples lesiones focales en colonias individuales; estas lesiones fueron creciendo progresivamente al tiempo que mataban las colonias. Para el año 2005, el 44% de los corales que se etiquetaron habían muerto; los restantes exhibían infecciones activas de BA (21%), o estaban en remisión (31.6%) pero habían perdido un promedio de >90% de su tejido. Aunque la incidencia de BA disminuyó a partir del 2000, la prevalencia de la plaga blanca (PB) fue inusualmente alta (4-12%) en el 2001 y 2005, provocando mortalidades recientes de hasta un 70% en las colonias afectadas. Las superficies muertas de Montastraea spp. han sido colonizadas por otros corales, incluyendo porítidos, agarícidos y otros fávidos, mientras que continúa la ausencia de reclutas de M. annularis (complejo). Si las enfermedades y otros estresores bióticos persisten en estos arrecifes, las poblaciones de M. annularis y M. faveolata podrían decaer de forma similar a como lo hicieron los acropóridos del Caribe durante la década de 1980.